Pemanfaatan Lahan Tidur Untuk Budidaya Kedelai Menuju Potensi Ekonomi Berkelanjutan Di Desa Sulkam, Kabupaten Langkat - Risky, Marshanda Sintia; Meizani, Anisa Meizani; Putri, Cici Amelia; Lesmana, Rivaldi; Panjaitan, Fahruza Rio Zilino; Sinuraya, Rizky Rahmananda; Ginting, Alvin; Ranita, Sylvia Vianty; Tanjung, Hasrudy; Hafni, Roswita (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
Sulkam Village is a forest village that still faces challenges in food security and community economic independence. Most residents rely heavily on palm oil and timber, whose prices fluctuate. However, the village boasts two hectares of unused land with the potential for productive use. Therefore, the “Tani Kedelai Ladang Harapan” (Hopeful Field Soybean Farming) program, implemented through community service activities, aims to diversify agricultural businesses and strengthen food security. The goal of this program is to provide the Sulkam Village community with the understanding and skills to utilize unused land through soybean cultivation and processing into value-added tempeh. The program’s methods include outreach, technical cultivation training, hands-on practice in hygienic tempeh production, and simple entrepreneurial mentoring. Results indicate an 80% increase in community skills in understanding soybean cultivation techniques and the tempeh production process. Furthermore, the program has successfully raised community awareness of the importance of agricultural business diversification and the potential for a sustainable economy based on local food. Therefore, the “Tani Kedelai Ladang Harapan” program can be a concrete step in improving the economy of the Sulkam Village community while strengthening the independence of forest villages through a sustainable bioeconomy.